2013
DOI: 10.5194/nhess-13-1501-2013
|View full text |Cite
|
Sign up to set email alerts
|

A study of the behavior of the terminator time shifts using multiple VLF propagation paths during the Pakistan earthquake (<i>M</i> = 7.2) of 18 January 2011

Abstract: Abstract. On 18 January 2011, at 20:23 UTC, an earthquake of magnitude 7.2 occurred in southwestern Pakistan (latitude 28°44' N, longitude 63°56' E) at a depth of 68 km. We present the results of the analysis of very low frequency (VLF) radio signals, received at three stations located in India. We analyze the VLF signals around this earthquake day and look for possible precursory effects of this earthquake. For our analysis, we use four different VLF propagation paths. These propagation paths are DHO–IERC (Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…In our past publications, the anomalies became evident from the received VLF signal amplitude/phase almost 0À4 days prior to the main event (Chakrabarti et al 2005(Chakrabarti et al , 2007(Chakrabarti et al , 2010Chakrabarti 2009, 2010;Ray et al 2010Ray et al , 2012Ray and Chakrabarti 2013;Sasmal et al 2014;Pal et al 2017). The methods that were used where VLF signal anomalies were detected before and during earthquakes are as follows: (a) The sunrise and sunset terminator time (SRT and SST) which are the minima in the signal amplitude when the D-layer is almost generated in the morning due to solar flux and it starts to disappear in the evening respectively executes shift towards night-time thereby increasing overall VLF day-length (Chakrabarti et al 2005;Chakrabarti 2009, 2010;Chakrabarti et al 2012;Chakraborty et al 2017), (b) unusual enhancements of D-Layer Preparation Time (DLPT) and D-Layer Disappearance Time (DLDT) (Chakrabarti et al 2007(Chakrabarti et al , 2010Sasmal and Chakrabarti 2010) during earthquake and (c) unusual night-time fluctuations (both positive and negative) before earthquakes (Ray et al , 2012.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…In our past publications, the anomalies became evident from the received VLF signal amplitude/phase almost 0À4 days prior to the main event (Chakrabarti et al 2005(Chakrabarti et al , 2007(Chakrabarti et al , 2010Chakrabarti 2009, 2010;Ray et al 2010Ray et al , 2012Ray and Chakrabarti 2013;Sasmal et al 2014;Pal et al 2017). The methods that were used where VLF signal anomalies were detected before and during earthquakes are as follows: (a) The sunrise and sunset terminator time (SRT and SST) which are the minima in the signal amplitude when the D-layer is almost generated in the morning due to solar flux and it starts to disappear in the evening respectively executes shift towards night-time thereby increasing overall VLF day-length (Chakrabarti et al 2005;Chakrabarti 2009, 2010;Chakrabarti et al 2012;Chakraborty et al 2017), (b) unusual enhancements of D-Layer Preparation Time (DLPT) and D-Layer Disappearance Time (DLDT) (Chakrabarti et al 2007(Chakrabarti et al , 2010Sasmal and Chakrabarti 2010) during earthquake and (c) unusual night-time fluctuations (both positive and negative) before earthquakes (Ray et al , 2012.…”
Section: Introductionmentioning
confidence: 93%
“…The methods that were used where VLF signal anomalies were detected before and during earthquakes are as follows: (a) The sunrise and sunset terminator time (SRT and SST) which are the minima in the signal amplitude when the D-layer is almost generated in the morning due to solar flux and it starts to disappear in the evening respectively executes shift towards night-time thereby increasing overall VLF day-length (Chakrabarti et al 2005;Chakrabarti 2009, 2010;Chakrabarti et al 2012;Chakraborty et al 2017), (b) unusual enhancements of D-Layer Preparation Time (DLPT) and D-Layer Disappearance Time (DLDT) (Chakrabarti et al 2007(Chakrabarti et al , 2010Sasmal and Chakrabarti 2010) during earthquake and (c) unusual night-time fluctuations (both positive and negative) before earthquakes (Ray et al , 2012. In the case-wise studies, effects of a particular earthquake event on different VLF propagation paths (transmitterreceiver) have been presented (Ray and Chakrabarti 2013;Sasmal et al 2014). Ray and Chakrabarti (2013) presented the seismo-ionospheric influences during the 2011 Pakistan earthquake (M ¼ 7.2) on four different propagation paths: DHO-IERC (Sitapur), VTX-Pune, VTX-ICSP (Indian Centre for Space Physics, Kolkata) and NWC-IERC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very Low Frequency (VLF)/Low Frequency (LF) radio sounding is one of the most successful tools for this research. There are several independent findings of anomalies in ELF/VLF/LF signal prior to seismic hazards (e.g., Gokhberg et al, 1989;Hayakawa et al, 1996Hayakawa et al, , 2003Molchanov et al, 1998;Molchanov and Hayakawa, 1998;Clilverd et al, 1999;Hayakawa and Molchanov, 2000;Chakrabarti et al, 2005Sasmal et al, 2009Ray et al, , 2012Ray et al, , 2013. Indian Centre for Space Physics (ICSP) (Lat.…”
Section: Introductionmentioning
confidence: 96%
“…It is also found that the depth of the earthquake epicentre plays an important role in the signal perturbations and the signal anomalies can be detectable with a higher confidence level for the shallow earthquakes (depth < 20 Km) ). Recently, Ray and Chakrabarti (2013) and Sasmal et al (2014) reported that there is a high possibility to predict the location of the earthquake epicentre by using the 'terminator time method' by analysing the data recorded from multiple propagation paths which intersects cover the earthquake locations. This study was done during two major earthquakes.…”
Section: Introductionmentioning
confidence: 99%